P-EGS11 The Theatre Training Checklist: A Toolkit to Revive Post Pandemic Operative Training. (16th December 2021) - Aldoori, Joanna; Robson, Andrew; Al-Attar, Adam; Burke, Josh; Giwa, Lolade; O'Regan, David; Peter, Mark
Abstract: Background: The COVID-19 pandemic has had a significant negative impact on operative surgical training, with trainee logbook numbers reduced by more than 50% compared to 2019. The operating theatre is expensive, costing approximately £1200 per hour to run. It is a crucial learning environment for many different trainees: anaesthetists, surgeons, operation department practitioners and surgical first assistants. For individuals to achieve their training requirements, the operating theatre as a training environment must be shared between all trainees. This requires excellent teamwork and leadership. The recovery phase of the COVID-19 pandemic is a unique opportunity to adopt novel training strategies. Methods: The Theatre Training Checklist is a simple framework that aims to facilitate awareness, understanding, coordination and cooperation of training for all members of the team (Figure 1). It is a practical strategy that can be adopted in any setting. Usually, trainers discuss informally with their trainees about their individual Skills, Experience, Expectationsand what is Achievable in a planned theatre list (SEEA). However, there currently is limited opportunity to discuss this between different disciplines and the wider team. This tool aims to refine communication, optimize training, manage expectations and ensure equity across the board. The checklist has been introduced and trialed locally. Results: The checklist is completed at the start of the list during the theatre brief. It identifies all trainees and their specific needs within the operating theatre session to the whole team. An agreed strategy is developed on how to achieve identified training goals (figure 2). Sometimes it may not be possible to allow a trainee to perform a particular procedure. However, other opportunities for training in theatre exist, such as: patient positioning, choice of equipment, types of techniques, discussions around consenting and complications etc. Feedback undertaken from the multiprofessional team after local trialing of the checklist has been positive. Conclusions: The Theatre Training Checklist aims to create dialogue and shared understanding of training needs among all parties within the operating theatre. The Theatre Training Checklist Toolkit is available for use and consists of the checklist tool and an instructional video. The Theatre Training checklist is being piloted in some centers and we hope to have the opportunity to present some early findings at AUGIS 2021.